2007
DOI: 10.1002/prot.21273
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray absorption and molecular dynamics study of cation binding sites in the purple membrane

Abstract: The present work describes the results of a study aimed at identifying candidate cation binding sites on the extracellular region of bacteriorhodopsin, including a site near the retinal pocket. The approach used is a combined effort involving computational chemistry methods (computation of cation affinity maps and molecular dynamics) together with the Extended X-Ray Absorption Fine Structure (EXAFS) technique to obtain relevant information about the local structure of the protein in the neighborhood of Mn(2+) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 58 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…For the bR labeled at residue 103C, ET is rather slow compared to α‐helix or β‐sheet‐mediated ET 2. 5 For a theoretical estimation of k ET , we used the experimentally proposed distances between bound Mn 2+ proposed to be located at the Asp36, Asp38 locus17 at the cytoplasmic side (15.1 Å) and the spin label inserted at the 103 residue and between bound Mn 2+ and the spin label inserted at the active site (22 Å),16 assuming that these distances are maintained when the Mn 2+ is displaced by [Ru(bpy) 3 ] 2+ . For these distances, α‐helix k ET values larger than 2×10 6 s −1 and 2×10 1 s −1 , respectively, can be predicted2 (see the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…For the bR labeled at residue 103C, ET is rather slow compared to α‐helix or β‐sheet‐mediated ET 2. 5 For a theoretical estimation of k ET , we used the experimentally proposed distances between bound Mn 2+ proposed to be located at the Asp36, Asp38 locus17 at the cytoplasmic side (15.1 Å) and the spin label inserted at the 103 residue and between bound Mn 2+ and the spin label inserted at the active site (22 Å),16 assuming that these distances are maintained when the Mn 2+ is displaced by [Ru(bpy) 3 ] 2+ . For these distances, α‐helix k ET values larger than 2×10 6 s −1 and 2×10 1 s −1 , respectively, can be predicted2 (see the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Such effect has been also used to explicate the response of other X-ray sensors like diamond dosimeters (Laub et al, 1997;Hoban et al, 1994) and carbon fiber radiation sensor (Ma et al, 2008). X-ray absorption studies on BR and purple membrane have shown absorption spectrum over a wide range of X-ray energies (Engelhard et al, 1987;Sepulcre et al, 2007). When the BR disk is irradiated by MV X-ray radiation, the absorption of the ionizing radiation causes a temporary change in the electrical conductivity of the BR thin film through the production of positive ions and electrons.…”
Section: Discussionmentioning
confidence: 97%
“…[2,5] For a theoretical estimation of k ET , we used the experimentally proposed distances between bound Mn 2+ proposed to be located at the Asp36, Asp38 locus [17] at the cytoplasmic side (15.1 ) and the spin label inserted at the 103 residue and between bound Mn 2+ and the spin label inserted at the active site (22 ), [16] assuming that these distances are maintained when the Mn 2+ is displaced by [Ru(bpy) 3 ] 2+ . For these distances, a-helix k ET values larger than 2 10 6 s À1 and 2 10 1 s À1 , respectively, can be predicted [2] (see the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%